Two Positive Periodic Solutions for a Neutral Delay Model of Single-Species Population Growth with Harvesting - Hui Fang (Discrete Dynamics in Nature and Society)
By coincidence degree theory for k-set-contractive mapping, this paper establishes a new criterion for the existence of at least two positive periodic solutions for a neutral delay model of single-species population growth with harvesting. An example is given to illustrate the effectiveness of the result.